Tutorial for Robotic Prostatectomy - Kenneth Jacobsohn; Margaret Mulligan; Lance Hampton; Scott Johnson (Association of American Medical Colleges, 2015)
Abstract Introduction In the medical education environment, the expectation to teach creatively and efficiently while maintaining or increasing productivity and complying with ACGME duty hour constraints is a taxing load for even the most dedicated physician. Additionally, duty hour constraints, evolving curricular experiences, high faculty expectations, and work-life balance issues challenge learners to be prepared and knowledgeable as they enter the operating room. This tutorial offers instructors educational tools that support the learning of medical students, residents, and novice robotic surgeons. Methods This tutorial is meant to be used repeatedly throughout a training program. We recommend that the tutorial and accompanying video, as well as the multiple-choice questions be utilized prior to entering the robotic surgical suite for the first time. The tutorial is meant to be read over and over during training as the learner progresses through the various steps of the operation. Dedicated video study and case observation will also be a key to mastery of robotic prostatectomy. The faculty instructor will need to regularly perform robotic prostatectomy to both help learners through challenging steps and cases, and emphasize the details they deem important on a case by case basis. The included Robotic Prostatectomy Posttest could also be utilized as a pretest with minor format and title changes. Results The tutorial and video have been distributed to our residents at the start of robotic rotations. The tutorial is required, and learners must demonstrate successfully completion all of the multiple-choice questions (Robotic Prostatectomy Posttest) prior to entering the robotic surgical suite. As residents progress through the learning process, they carry this tutorial with them. It is common to see them sitting with a video and the tutorial, making notes. Discussion This tutorial has significantly shortened the learning curve for our residents. Residents have demonstrated advanced knowledge related to their roles and the roles of others in the robotic operating room suite, knowledge of access and port placement for robotic procedures, and knowledge of the elements of robotic prostatectomy. When a learner is struggling with the operation or a given step, it is useful to have him or her review this tutorial and then have the instructor sit with the learner in a dedicated video review session to help clarify the details the learner is overlooking or having difficulty with.